Kemampuan Pemecahan Masalah: Analisis Pada Siswa SMP - Anwar, Azwar; Margawari Novel; Suharni (Mandalika Mathematics and Educations Journal, 2025)
The aim of this qualitative research is to describe students' problem solving abilities in solving story problems in transformation material, namely reflection and translation. Problem solving ability has 4 indicators, namely: 1) identifying problems, 2) making plans, 3) implementing plans, and 4) checking again. The research was carried out in the odd semester of the 2024/2025 academic year. The research subjects consisted of 31 students in class IX-6 of SMPN 4 Tarakan who had been taught Transformation material. Then 3 students were selected who had problem solving abilities at high, medium and low levels. Data collection techniques used problem solving ability tests and interviews. This research's data analysis techniques include data reduction, data presentation, and drawing conclusions/verification. The results of the research show that students at the high level are able to fulfill all indicators of the 4 indicators of problem solving ability, namely indicators 1, 2, 3, and 4. Students at the medium level are able to fulfill 3 of the 4 indicators of problem solving ability, namely indicators 1, 2, and 3 . Students at low levels are only able to fulfill 2 indicators of problem solving ability, namely indicators 1 and 3.